Children's literature : a reader's history, from Aesop to Harry Potter - Lerer, Seth, 1955- (University of Chicago Press, 2008)
Children's Literature charts the makings of the Western literary imagination from Aesop's fables to Mother Goose, from Alice's Adventures in Wonderland to Peter Pan, from Where the Wild Things Are to Harry Potter. Seth Lerer here explores the iconic books, ancient and contemporary alike, that have forged a lifelong love of literature in young readers during their formative years. Along the way, Lerer also looks at the changing environments of family life and human growth, schooling and scholarship, and publishing and politics in which children found themselves changed by the books they read. This ambitious work appraises a broad trajectory of influences--including Shakespeare's plays, John Locke's theories of education, Darwin's On the Origin of Species, and the Puritan tradition--which have each shaped children's literature through the ages as well.--From publisher description.